Oxidative stress markers and antioxidant defense in hibernating common Asian toads, Duttaphrynus melanostictus - Sahoo, Deba Das; Patnaik, Prabhati (Archives of Biological Sciences, 2020)
Paper description: In hibernating common Asian toad, in spite of metabolic depression, low body temperature, and slow breathing, oxidative stress was observed. Oxidative stress markers were at higher levels in liver and brain tissues. Increased lipid peroxidation, protein carbonylation and oxidized/reduced glutathione ratio were accompanied by augmented non-enzymatic antioxidant defense which counteracts the oxidative assault in liver and brain tissues during hibernation. Abstract: To assess the oxidative assaults and antioxidant defense, oxidative stress markers, including lipid peroxidation level, protein carbonylation level, GSSG/GSH ratio and nonenzymatic antioxidants such as total glutathione, ascorbic acid and uric acid, in liver and brain tissues of hibernating common Asian toads, Duttaphrynus melanostictus, were compared with toads during active periods. Oxidative stress was found in both liver and brain tissues of hibernating common Asian toads in spite of depressed metabolism and low oxygen consumption. Significantly higher lipid peroxidation, protein carbonylation and an increased GSSG/GSH ratio were found in liver and brain tissues of hibernating toads, indicating oxidative stress. To counteract the stress, ascorbic acid was increased significantly in the liver and brain tissues of hibernating individuals in comparison to individuals during active periods. The uric acid level decreased in both the liver and brain tissues of hibernating toads, which may be due to its decreased rate of synthesis because of low xanthine oxidase activity at low body temperature and hypometabolism. The common Asian toad faced oxidative stress during hibernation, which was counteracted by augmented nonenzymatic antioxidant defense. https://doi.org/10.2298/ABS190605062S Received: June 5, 2019; Revised: August 24, 2019; Accepted: September 9, 2019; Published online: September 25, 2019 How to cite this article: Sahoo DD, Patnaik P. Oxidative stress markers and antioxidant defense in hibernating common Asian toads, Duttaphrynus melanostictus. Arch Biol Sci. 2020;72(1):23-30.